ANALISIS KUALITAS TUGAS FASHION PHOTOGRAPHY PADA MATA KULIAH PUBLIKASI MODE - Raya Putrianda; Winwin Wiana (Universitas Pendidikan Indonesia, 2016)
Fashion Photography is a student assignment on the subject of mode publication, photographed models with all fashion instrument to inform or publish things about fashion. The research purposes is to obtain data on the quality of fashion photography assignment in term of several aspects such as camera function, composition, lighting, camera lens focus, poses, expressions, photo effects and integrates the principles of art photography. The method used in this research is descriptive analytic with purposive sample from student of design management who attended and completed the task of making fashion photography course on mode publication subject, which amounts to 30 archive fashion photography assignment. The result showed that more than half of student are able to set shutter speed, shooting distance, and poses in favor of fashion display characteristic’s, and adjust the expressions with the clothing displayed with very high quality. Half of the students have been able to set the focus to produce clear image details with very high quality. Less than half students are able to exploit of the light source with a very high quality, integrating principle of unity with high quality and setting photo effects with low quality.